Biography of Luvsandambadarjay, the Nobleman, the Wise Man, the Great Treasure of the Religious Sect, the Mirror of Chandmani - Torguud, Otgonbayar (Tibetan Studies, 2024)
No abstract in English Шашны садан Ялгуусан эрдэнэ мэргэн бандида хутагт Лувсандамбадаржаагийн намтар Чандманийн толь хэмээх оршвой